Influence of Solvent on the Component Composition and Antioxidant Properties of Apricot Cake (Prunus armeniaca L.) Extracts - A. S. Shakun; V. I. Vorobyova; O. E. Chygyrynets; M. I. Skiba (Journal of Chemistry)
Antioxidants of natural origin which are based on agroprocessing waste appear as substance with high performance properties. They have complicated structure and contain a complex of biologically active compounds. This is why research of the above is particularly relevant in current competitive market. When working with plant raw materials and isolation of valuable compounds, the urgent issue is the choice of the method (extraction method) and extractant, which will ensure a maximum release of chemically active compounds. Known solvents such as methanol, ethanol, hexane, diethyl ether, and mixtures thereof are usually used for recovery. The purpose of this research was to study the effect of selected nonpolar solvents on the phytochemical composition and the antioxidant capacity of Prunus armeniaca L. Extracts were obtained using ethanol, silicone, propan-2-ol, and mixtures of ethanol silicone and propan-2-ol with silicone. In the obtained extracts, identification of the sequestered chemically active compounds was carried out by means of chromatography, mass spectrometry, and IR and UV spectrometry, and the extracts were evaluated on antioxidant properties. Various extracts showed varying degrees of antioxidant activity in various test systems, depending on the concentration. Since various antioxidant compounds have different mechanisms of action, several methods have been used to evaluate the effectiveness of antioxidant extracts. The results showed that the test solvents play an important role in the extraction of the plant material into the component composition, as well as the antioxidant ability of Prunus armeniaca L.